2023
DOI: 10.1021/acsami.3c06601
|View full text |Cite
|
Sign up to set email alerts
|

High-Precision and Rapid Direct Laser Writing Using a Liquid Two-Photon Polymerization Initiator

Abstract: Two-photon polymerization based direct laser writing (DLW) is an emerging micronano 3D fabrication technology wherein two-photon initiators (TPIs) are a key component in photoresists. Upon exposure to a femtosecond laser, TPIs can trigger the polymerization reaction, leading to the solidification of photoresists. In other words, TPIs directly determine the rate of polymerization, physicochemical properties of polymers, and even the photolithography feature size. However, they generally exhibit extremely poor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Thanks to their strong optical nonlinearities, traditional MPL-based 3D printing has successfully achieved high-resolution features of submicrometers . Moreover, more recent studies have demonstrated ongoing advancements in MPL technology, achieving feature sizes below 100 nm. However, many research groups that assess the effectiveness of PIs by determining TPA cross sections using high-repetition rate (as, e.g., MHz) femtosecond (fs) laser sources have led to the erroneous conclusion that a high cross section is not responsible for high efficiency. Primarily, under such experimental conditions, unwanted thermal effects inevitably manifest, obscuring pure electronic response contributions to the NLO response . As a result, erroneous extremely large values of the TPA cross section have been reported.…”
Section: Introductionsupporting
confidence: 71%
“…Thanks to their strong optical nonlinearities, traditional MPL-based 3D printing has successfully achieved high-resolution features of submicrometers . Moreover, more recent studies have demonstrated ongoing advancements in MPL technology, achieving feature sizes below 100 nm. However, many research groups that assess the effectiveness of PIs by determining TPA cross sections using high-repetition rate (as, e.g., MHz) femtosecond (fs) laser sources have led to the erroneous conclusion that a high cross section is not responsible for high efficiency. Primarily, under such experimental conditions, unwanted thermal effects inevitably manifest, obscuring pure electronic response contributions to the NLO response . As a result, erroneous extremely large values of the TPA cross section have been reported.…”
Section: Introductionsupporting
confidence: 71%
“…However, its speed is naturally slow, necessitating faster scanning or multibeam approaches for large-scale fabrication. Therefore, to transition from laboratory research to industrial applications, mass production becomes imperative, which can be achieved through the development of extreme sensitive photoresists [245,246] and high-speed TPL technologies [247,248]. Various scanning schemes, including single beam writing with stage scanning, galvanometer scanning, rotating mirror scanning, or acousto-optic deflector (AOD) scanning, have been explored to increase speed.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches for increasing the throughput include increasing the scanning speed of serial writing, parallelizing the writing, and combining the previous two approaches [ 21 , 22 , 23 , 24 ]. It is noteworthy that recent studies have demonstrated high scanning speeds up to and exceeding 1 m s −1 with serial TPL [ 25 , 26 , 27 , 28 , 29 ]. However, the printing of 3D structures with sub-100 nm feature sizes has not yet been demonstrated at these high speeds.…”
Section: Introductionmentioning
confidence: 99%